Life-threatening tension pneumothorax after unsuccessful tracheostomy tube exchange in a trauma patient - A case report - - Kwon, Min A (Anesth Pain Med (Seoul), 2020)
BACKGROUND: Tracheostomy tube exchange is a common and safe procedure. However, when the tracheocutaneous tract is not completely mature, cannula exchange or endotracheal tube insertion via the tracheostomy site can rarely induce life-threatening complications, including subcutaneous emphysema, loss of airway, tension pneumothorax, and pneumoperitoneum. CASE: We report a case of life-threatening tension pneumothorax developed during tracheostomy tube exchange with a reinforced endotracheal tube for a planned facial surgery after recent tracheostomy in a trauma patient. CONCLUSIONS: Understanding of the pathogenesis and the use of preventive strategies based on it are expected to provide safer and more effective anesthetic management to patients with tracheostomy.